Maritime Infrastructure Development and its Impact on National Economic Growth - Sibali, Alwi; Jainuddin, Jainuddin (Economics and Digital Business Review, 2024)
Maritime infrastructure development plays a strategic role in strengthening the national economy, especially in an archipelagic country like Indonesia. This article explores the relationship between investment in maritime infrastructure, such as ports, shipping lanes and logistics facilities, and national economic growth. Through secondary data analysis and case studies of major ports in Indonesia, the research finds that improvements in port capacity and efficiency contribute significantly to increased trade volumes, logistics efficiency, and international competitiveness. Adequate maritime infrastructure is able to reduce logistics costs, speed up delivery times, and improve inter-island connectivity, thereby supporting regional and national economic growth. In addition, this article also discusses the challenges faced in developing maritime infrastructure, including issues of financing, regulation, and environmental impacts. Sustainable financing and private sector involvement through public-private partnership schemes are considered crucial in accelerating infrastructure development. Clear and consistent regulations are also needed to create a conducive investment climate. On the other hand, the environmental impacts of port and shipping line development must be well managed to ensure long-term sustainability. The results show that planned and integrated maritime infrastructure development can drive sustainable economic growth, create jobs and improve people's welfare. Policy recommendations include increased co-operation between the public and private sectors, as well as the adoption of new technologies to improve operational efficiency. Thus, maritime infrastructure development not only improves national logistics performance but also contributes to stability and sustainable economic growth.